1981
DOI: 10.1002/ana.410100304
|View full text |Cite
|
Sign up to set email alerts
|

Intensive evaluation of referred unclassified neuropathies yields improved diagnosis

Abstract: Intensive evaluation of 205 cases of undiagnosed neuropathy in a center with special approaches and facilities permitted classification of 76% of the patients. Inherited disorders accounted for 42% of the series, 21% of the patients were shown to have inflammatory-demyelinating polyradiculoneuropathy, and 13% had neuropathies associated with other disorders. A considerable improvement in diagnosis was possible from evaluation of the kin of the patients with undiagnosed neuropathy. Analysis of the frequency and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
151
1
9

Year Published

1989
1989
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(166 citation statements)
references
References 3 publications
5
151
1
9
Order By: Relevance
“…Even in patients with type 2 diabetes, glycemic control has only a small effect on the prevention of peripheral neuropathy 6. Furthermore, a significant proportion of patients with peripheral neuropathy have no known underlying cause 7, 8, 9, 10. Therefore, a better understanding of the underlying causes is needed to inform the development of new disease modifying treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Even in patients with type 2 diabetes, glycemic control has only a small effect on the prevention of peripheral neuropathy 6. Furthermore, a significant proportion of patients with peripheral neuropathy have no known underlying cause 7, 8, 9, 10. Therefore, a better understanding of the underlying causes is needed to inform the development of new disease modifying treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Hereditary polyneuropathy represents 42% of 205 cases of undiagnosed neuropathy 20 and 30% of 402 consecutive patients with polyneuropathy 21 in two separate neuropathy specialty clinics. Thus, hereditary polyneuropathy was recognized to account a Extrapolated total number and mutation frequencies recalculated for the total number.…”
Section: Discussion Prioritizing Molecular Testingmentioning
confidence: 99%
“…This estimate is, however, based on very uncertain assumptions. A recent report stated that CIDPrepresents a significant number of initially-undiagnosed acquired neuropathies, with estimates varying from 10 to 20% (9). Moreover, our recent survey (10) revealed that the prevalence rate is roughly estimated to be around 2 to 3 per 100,000 of population in the northern Honshu area.…”
mentioning
confidence: 81%